Meteorological data at the Thule High Arctic Atmospheric Observatory (THAAO_Met) - Muscari, Giovanni; Di Sarra, Alcide; Di Iorio, Tatiana; Pace, Giandomenico; Meloni, Daniela; Sensale, Gianpaolo; Calì Quaglia, Filippo; Iaccarino, Antonio (2018)
Meteorological data at the Thule High Arctic Atmospheric Observatory (THAAO_Met)